Imperative Aspects of Calf Rearing: An Overview - , Niharika Thakur; , Rajesh Kasrija; , Parminder Singh (Archives of Current Research International, 2025)
Farmers frequently ask about the best management practices for raising calves. Effective management practices, the minimally stressful environment, and the right feed supplementation can produce a healthy calf that will be productive once it enters the milking herd in the future, as previous studies have consistently shown and verified. Therefore, determining the optimum method for raising calves in each area is important. There have been numerous researches done over the years to determine the optimal management techniques for effective calf rearing. Due to the high expense of rearing calves, it is essential to establish the most effective means of ensuring sustainable techniques of raising calves that may ultimately prove to be profitable for dairy producers. Various key points in the calf rearing such as post-partum neonatal calf management, the correct management of the naval cord, colostrum feeding along with the housing and feeding requirements are discussed in the paper. This review paper aims to identify the most effective scientific management techniques for calf rearing from birth till it matures into a heifer, appropriate nutrition for the young calf, and the best approaches to maintain calf healthy and free from infectious diseases and stress.